Regulation of the T Cell Response by CD39 - Takenaka, Maisa C.; Robson, Simon; Quintana, Francisco J. (Trends in immunology, 2016)
The ectonucleoside triphosphate diphosphohydrolase 1 (ENTPD1, or CD39) catalyzes the phosphohydrolysis of extracellular ATP (eATP) and ADP (eADP) released under conditions of inflammatory stress and cell injury. CD39 generates AMP, which is in turn used by the ecto-5′-nucleotidase CD73 to synthesize adenosine. These ectonucleotidases have a major impact on the dynamic equilibrium of proinflammatory eATP and ADP nucleotides versus immunosuppressive adenosine nucleosides. Indeed, CD39 plays a dominant role in the purinergic regulation of inflammation and the immune response because its expression is influenced by genetic and environmental factors. We review the specific role of CD39 in the kinetic regulation of cellular immune responses in the evolution of disease. We focus on the effects of CD39 on T cells and explore potential clinical applications in autoimmunity, chronic infections, and cancer. CD39 regulates T cell activation, polarization, and stability by scavenging immunostimulatory extracellular ATP (eATP) and promoting the generation of immunosuppressive adenosine. CD39 impacts T cell response by acting directly on T cells, and also indirectly by modulating the activity of antigen-presenting cells. The regulation of CD39 expression by cytokines and other immunological stimuli modulates the immune response in the context of inflammation, infections, and cancer. CD39-targeted approaches offer new avenues for the therapeutic modulation of the immune response in autoimmunity, infections, and cancer.